On the summability of double Walsh - Fourier series of functions of bounded generalized variation - Goginava, U. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
The convergence of Cesaro means of negative order of double Walsh-Fourier series of functions of bounded generalized variation is investigated.